Acute Gastroenteritis Outbreak in Meghalaya, India - Shylla, Badondor; Syiemlieh, Alisha J.; Nongdhar, Jurysha (Indian Journal of Nursing Sciences, 2024)
background: Between January and February 2018, an outbreak of acute gastroenteritis (AGE) was reported in Nongpoh Civil Hospital, Ri-Bhoi District in Meghalaya among the under five children. The mothers reported that the children developed diarrheal diseases after receiving polio drops administered during Intensified Pulse Police Immunization (IPPI) first round (January 29–31, 2018). Objective of the study: To describe the outbreak and to prevent and control the outbreak. Methods: This survey was conducted among the under-five children on February 2, 2018 reported with increased AGE cases. Rapid Response Team from District Surveillance Unit, Ri-Bhoi generated an early warning signal and conducted an epidemiological investigation. Parents alleged that polio drops administered during IPPI first round caused illness. All the under-five children admitted and registered in in-patient were investigated. A total of 85 cases fit the case definition of AGE. Results: The median age of these cases was 1 year 2 months (1 month, 5 years) with 44 (51.7%) male and 41 (48.2%) female. All three stool samples (100%) tested positive for Rotavirus Ag. Similarly, all two water samples (100%) showed coliforms beyond permissible values. The present outbreak highlights that a high proportion of infants who were affected from Nongpoh, Umtasor, and Umkaduh. Conclusion: The identified causative agent is Rotavirus Ag. Polio vaccine was not associated with illness